Effects of adverse childhood experiences and personal resilience on household emergency preparedness: considerations for disaster planning - Heagele, Tara; Samuels, William Ellery; Kaplan, Sarah; Wilcox, Lisa; Amberson, Taryn; McNeill, Charleen; Adams, Lavonne M. (Frontiers in Public Health, 2025)
IntroductionAdverse childhood experiences (ACEs) are potentially traumatic events occurring during childhood that can affect adulthood health and wellness, including preparedness for disasters. This study aimed to understand how ACEs, personality traits, personal resilience, and healthcare provider discussions of preparedness affect household emergency preparedness to inform interventions for individuals with a history of ACEs.MethodsThis cross-sectional study was conducted through an internet-based survey of 311 US adults using six evidence-based instruments: ACEs Questionnaire, Big Five Inventory, Chapman University Survey on American Fears, Grit-S, Brief Resilient Coping Scale, and the Household Emergency Preparedness Instrument.ResultsAlthough most participants had experienced at least one ACE, there was no significant relationship between ACEs and disaster preparedness. Income, confidence in preparedness, and emotional reactivity were more predictive.ConclusionFindings can guide the development of tailored community interventions and policies to improve disaster preparedness among individuals with a history of childhood trauma.